Studies on the germination of barley - Macleod, Anna M. (The University of Edinburgh, 1967)
I Studies on the Free Sugars of the Barley Grain. I. Historical Survey. J. Inst. Brew., 1952, 58, 270. || II Studies on the Free Sugars of the Barley Grain. II. Distribution of the Individual Sugar Fractions. J. Inst. Brew., 1952, 5§, 363. || Ill Studies on the Free Sugars of the Barley Grain. III. Changes in Sugar Content during Malting (with D. C. Travis and D.G. Wreay). J, Inst. Brew., 1953# 59# 154. || IV Studies on the Free Sugars of the Barley Grain. IV. Low-molecular Fructosans. J. Inst. Brew., 1953, 59, 462. || V Raffinose Metabolism in Germinating Barley. New Phytol., 1957, 56, 210. || VI Comparative Studies of Embryo and Endosperm (with H. McCorquodale). J. Inst. Brew.. 1958, 64, 112. || VII Cellulose Distribution in Barley (with J. P. Napier). J. Inst. Brew., 1959, 65, 188. || VIII Studies on the Free Sugars of the Barley Grain. V. Comparison of Sugars and Fructosans with those of other Cereals (with I. A. Preece). J. Inst. Brew., 1954, 60, 46. || IX Barley Carbohydrate Metabolism in Relation to Malting. Wallerstein Lab. Commun., I960, 25, 87. || X Lipid Metabolism in Germinating Barley. I. The Fats (with H. B. White). J. Inst. Brew., 1961, 67, 182. || XI Lipid Metabolism in Germinating Barley. II. Barley lipase (with H, B. White). J. Inst. Brew., 1962, 68, 487. || XII Water-soluble Carbohydrates of Seeds of the Gramineae (with H. McCorquodale). New Phytol., 1958, 57, 168. || XIII Trisaccharides of Lolium and Festuca (with H, McCorquodale). Nature, Lond., 1958, 182, 8.15 || XIV Hemicellulases of Bromus Seeds (with R. Sandie). New Phytol., 1961, 60, 117. || XV Effects of Gibberellic acid on Barley Endosperm (with A. S. Millar). J. Inst. Brew., 1962, 68, 522. || XVI Ultra-structure of Caryopses of the Gramineae. I. Aleurone and Central Endosperm of Bromus and Barley. (with C. S. Johnston and J. H. Duffus). J. Inst. Brew., 1964, JO, 505. || XVII Gibberellic Acid In the Germination of Barley (with J. H. Duffus and A. S. Millar). Proc. Eur. Brew. Conv. Brussels, 1965, 85. || XVIII Development of Hydrolytic Enzymes in Germinating Grain (with J. H, Duffus and C, S. Johnston). J. Inst. Brew.. 1964, JO, 521. || XIX The Embryo as an Activator of Gibberellic-acid-induced α-Amylase (with J. H. Duffus and D. J. L. Horsfall). J. Brew., 1966, 72, 36. || XX The Embryo of Barley in Relation to Endosperm Modification (with G. H. Palmer). J. Inst. Brew., 1966 (In press). || XXI On Barley. Trans, bot. Soc. Edinb., 1961, 39, 247. || XXII The Physiology of Malting. J. Inst. Brew., (in press).